PENGARUH PENGUNGKAPAN SUKARELA, UKURAN PERUSAHAAN, LEVERAGE , MANAJEMEN LABA DAN RISIKO PASAR TERHADAP BIAYA MODAL EKUITAS ( Studi Empiris Pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2012 – 2016 ) - Rika, Rika; Rusli, Amries; Adhitya, Adhitya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The study was conducted to analyze the effect of voluntary disclosure, firm size, leverage, earnings and risk management (stock beta) on equity capital cost s(Empirical Study on Basic and Chemical Industry Sector Listed on Indonesia Stock Exchange period 2012-2016). The population used in this research is the Basic and Chemical Industry Sector Companies Listed on the Indonesia Stock Exchange period 2012-2016, while the sampling technique is done by purposive sampling. Data analysis method used is quantitative analysis by using multiple regression analysis.From the research results it is known that there is a significant influence between voluntary disclosure (X1), firm size (X2), leverage (X3), earnings management (X4) and market risk (X5) to capital equity cost (Empirical study on basic industry sector and chemicals listed on Indonesia Stock Exchange period 2012-2016). In this study has the limitations among other research population is limited to basic industry and chemical companies listed on the Indonesia Stock Exchange which published the financial statements of the period 2012 to 2016. Independent variables in this study only five variables used variables that are suspected to affect cost of equity capital. For that it is advisable for further researchers to expand the object of research. For the Company should pay attention to the growth of one by looking at the results of company performance, especially financial statements. For Investors should be more careful in assessing the company's financial statements, especially related to financial information so that investment decisions taken will not cause regret in the future.Keywords : voluntary disclosure, firm size, leverage, earnings management and market risk on the cost of equity capital